C-type lectin (CTL) and sialic acid-binding lectin (SABL) from Venerupis philippinarum: Function on PAMP binding and opsonic activities in immune responses. Issue 133 (February 2023) - Liu, Xiaohan; Gao, Jiqing; Wei, Xiao; Zhang, Xinze; You, Liping; Liu, Yuanjin; Chen, Lizhu; Liu, Caili; Sun, Chunxiao; Tian, Xiuhui; Zhou, Quanli; Zhang, Xiaomin
Abstract: Lectins are a superfamily of carbohydrate-recognition proteins that bind to specific carbohydrate structures and play significant roles in immune recognition and clearance of invaders. In the study, we investigated the potential mechanisms of PAMP binding and opsonic activities of a c-type lectin and a sialic acid-binding lectin from manila clam Venerupis philippinarum (designed as VpCTL and VpSABL). Both recombinant proteins (rVpCTL and rVpSABL) could bind LPS, PGN, glucan and zymosan in vitro . Coinciding with the PAMPs binding assay, a broad agglutination spectrum was displayed by rVpSABL including gram-positive bacteria Staphyloccocus aureus, gram-negative bacteria Escherichia coli, Vibrio parahaemolyticus, Vibrio harveyi, Pseudomonas putida, Proteus mirabilis and fungi Pichia pastoris, while no agglutinative activities on P. mirabilis and P. putida was observed in rVpCTL. Moreover, the phagocytosis and encapsulation ability of hemocytes could be significantly enhanced by rVpCTL and rVpSABL. More remarkable, VpCTL and VpSABL were highly detected in all the examined tissues, especially in gills and hepatopancreas. All the results showed that VpCTL and VpSABL could function as pattern recognition receptors (PRRs) with distinct recognition spectrum, perhaps involved in the innate immune responses of V. philippinarum . Highlights: Both rVpCTL and rVpSABL could bind LPS, PGN, glucan and zymosan in vitro. A broad agglutination spectrum was displayed by recombinant lectins, especially by rVpSABL. The phagocytosis and encapsulation ability of hemocytes could be significantly enhanced by rVpCTL and rVpSABL.